Spontaneous formation and reversible transformation between achiral J- and chiral H-aggregates of cyanine dye MTC. Issue 20 (11th April 2019) - Guan, Ai-Jiao; Zhang, Jing-Tao; Wang, Li-Xia; Cui, Jie; Xiang, Jun-Feng; Sun, Xin; Chen, Kuo; Li, Qian; Tang, Ya-Lin
Abstract : Spontaneous transformation from achiral J-aggregates to chiral H-aggregates of cyanine dye MTC was investigated. Abstract : Chirality at a supramolecular level is currently attracting great attention attributed to rapid developments in supramolecular chemistry. Herein, we report a new type of chiral self-assembly based on the cyanine dye MTC. The chiral H-aggregates of MTC could form spontaneously from achiral J-aggregates, and could return back to achiral J-aggregates in high concentration on increasing the solution temperature.